Analysis of impaired nonverbal communication in people with autism spectrum disorders - Vitásková, Kateřina; Říhová, Alena (Social Welfare: Interdisciplinary Approach, 2013)
The impairment of nonverbal communication in people with autism spectrum disorders (ASD) is a differential-diagnostic criterion that predicts their development and, at the same time, it serves as a striking determinant of their socialization. In this paper, we focus on the analysis of nonverbal forms of communication in a group of individuals diagnosed with ASD. The presented conclusions are partial results of the specifi c research grant (IGA PdF_2012_021, researcher: Kateřina Vitásková).